Apostille As A Mechanism For The Recognition Of Foreign Official Documents In The Republic Of Uzbekistan - Allaberganova Nodira Maxmud qizi (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
This article analyzes the apostille system as a key element of international legal circulation of documents, with specific reference to the Republic of Uzbekistan. The study examines the legal nature and functions of the apostille under the Hague Convention of 1961, emphasizing its role in replacing consular legalization with a simplified authentication mechanism. Particular attention is given to the division of responsibilities between the state of origin and the state of destination of official documents. The article also explores the national implementation of the Convention in Uzbekistan, including institutional arrangements and administrative practice. Special focus is placed on recent developments related to electronic apostilles. The study concludes that the apostille system enhances legal certainty while facing ongoing technological and coordination challenges.